Mixed language programming - Telles, Matthew A. (M&T Books, 1994)
Teaches intermediate- to advanced-level programmers how to combine visual programming environments, traditional languages, and existing applications. Students learn to create a complete data-entry system; a report printer/viewer; and utilities in Windows, incorporating Visual Basic, Borland C++, Visual C++, and Microsoft Word into a Windows program. The companion disk includes sample programs and code fragment. Lacks a bibliography.